Lazer noturno e juventudes: uma etnografia na Rua da Lama - Kuster, Saulo (2021)
The study questions how the regular visitor’s nighttime leisure routes of Rua da Lama constituted. The methodology used was ethnography, taking as main reference the concept of "dense description" of anthropologist Clifford Geertz, and as research instruments; observations, notes, informal conversations and semi-structured interviews. For this, I experienced the forms of leisure and its routes in the events, in the bars, in the sidewalks and on the street, in 2019. During the year 2020 and part of 2021, the moment of COVID-19 pandemic, the research was transferred, at first, to the virtual environment, where I investigated the interlocutor’s leisure previously contacted. Later, I started to reinsert myself in the research field, mixing virtual and in-person protocols. The results of this inquiry, shows that Rua da Lama is a complex environment, which protects several forms of leisure in its nights. This makes nighttime leisure in the place, for some people, synonymous with chaos, while for others, it is a form of democratization of the surroundings. The evening routes takes as its main purpose, the search for continuity of fun started in a first leisure space, being constituted/mobilized by aspects related to the compatibility of musical tastes and audience, in addition to being related to purchasing power. Its visitors appropriates Rua da Lama as a central place for leisure and as a place to carry out warms up and nightcaps. During the period of social isolation, I could perceived the interlocutors' difficulty in managing their own time. This situation created some confusion between work time and time that was formerly used for leisure. At the time that people started to come back to Rua da Lama evening, I noticed characteristics of the moment of “normality” and reminiscences of the pandemic period. This means that, in some cases, the nocturnal leisure route does not exist, or, when it occurs, it is a derived night leisure route, which instead of connecting to nightclubs (as it is traditional), connects to social and the clandestine night parties.